2021
DOI: 10.1371/journal.pone.0251251
|View full text |Cite
|
Sign up to set email alerts
|

Perceived built environment, health-related quality of life and health care utilization

Abstract: Previous research has shown that the built environment plays a crucial role for health-related quality of life (HRQoL) and health care utilization. But, there is limited evidence on the independence of this association from lifestyle and social environment. The objective of this cross-sectional study was to investigate these associations, independent of the social environment, physical activity and body mass index (BMI). We used data from the third follow-up of the Swiss study on Air Pollution and Lung and Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although this is a new finding, the National Recreation and Park Association previously conducted a survey on the perception and use of local recreation and park services among Americans and showed that even non-users of parks believed that having a local park, playground, or open space in their neighborhood was important to their personal and community wellbeing ( 48 ). In another study of Switzerland adults, higher satisfaction with the living environment and perception of access to green spaces were associated with higher health-related QoL ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a new finding, the National Recreation and Park Association previously conducted a survey on the perception and use of local recreation and park services among Americans and showed that even non-users of parks believed that having a local park, playground, or open space in their neighborhood was important to their personal and community wellbeing ( 48 ). In another study of Switzerland adults, higher satisfaction with the living environment and perception of access to green spaces were associated with higher health-related QoL ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor mobility is a crucial subject that has the potential to stimulate or inhibit autonomy and hence to compel or avoid impairment [123]. Walkable green streets, access to public spaces, and park density may contribute to older adults' health and health-related QoL (HRQOL) [124][125][126]. Other factors that promote health among older people include increased perceived diversity, safety, aesthetics, accessibility of neighbourhood amenities, leisure, social interaction, and less reported noise [124,125,127,128].…”
Section: Fostering Good Healthmentioning
confidence: 99%
“…Walkable green streets, access to public spaces, and park density may contribute to older adults' health and health-related QoL (HRQOL) [124][125][126]. Other factors that promote health among older people include increased perceived diversity, safety, aesthetics, accessibility of neighbourhood amenities, leisure, social interaction, and less reported noise [124,125,127,128]. In addition, one study showed a solid correlation between lower depressive symptoms and the amount of urban greenery and commercial space within a 500 m buffer [129].…”
Section: Fostering Good Healthmentioning
confidence: 99%
“…Neighborhoods with functioning social organizations and desirable accessibility show high utilization of services for frail older adults with complex needs dwelling at home ( 33 ). In addition, the built environment, such as transportation and green spaces, affect local health care utilization and residents' health and wellbeing ( 34 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%